The Story and the Telling – Perspectives on Training in Contemporary Puppetry (Móin-Móin - Revista de Estudios sobre Teatro de Formas Animadas, 2018)
Quality design and virtuoso performance do not always produce a good play.They are not enough; neither is the sum total of the stage elements. Staging is a craft primarily focused on constructing complex evolving relationships between the various elements: between the story and the interpretation, the puppets and the performers, the characters and their function, and between the story and the narration. This article looks at the teaching practices established by Ophrat through four exercises dealing respectively with (a) the function of the body as it reflects on the relationship of the performer and the puppets, (b) the separated use of sound and action, being originated from different sources,(c) The idea of duality of the puppet as major dramatic role, and (d) understanding that everything in puppet theater can be manipulated, including space.Keywords: Visual Theater. Story telling. Object-subject.